GCT-14. The Impact of Residual Disease on the Outcomes of Central Nervous System Germinomas – A Single Institution Experience. (3rd June 2022) - Cantor, Evan; Cochrane, Anne; Ogle, Andrea; Meyer, Ashley; Brossier, Nicole M; Shatara, Margaret; Cluster, Andrew; Abdelbaki, Mohamed S
Abstract: BACKGROUND: CNS Germinomas are highly radio-sensitive tumors with an excellent survival rate of more than 90%. The current standard of care combines chemotherapy with reduced-dose radiotherapy to minimize the adverse effects and long-term effects associated with radiotherapy. In the latest Children's Oncology Group clinical trial (ACNS1123 stratum 2), patients with residual or progressive disease following chemotherapy can be considered for a "second-look" surgery to assess tumor viability. Patients with residual disease who do not undergo second-look surgery receive 24 Gy of whole ventricular radiation with a 12 Gy boost compared to 18 Gy plus boost given to patients in complete remission or without viable tumor on second-look. Conversely, the International Society of Paediatric Oncology (SIOP) protocol does not stratify based on response to chemotherapy, and the Korean SMC GCT trial uses 18 Gy CSI plus boost for all patients regardless of chemotherapy response. METHODS: Single center retrospective chart review of germinoma patients treated at St Louis Children's Hospital between 2011 and 2021. RESULTS: We analyzed data for all 15 germinoma patients treated between 2011 and 2021. Five patients had residual disease following chemotherapy. Of these five, one had complete remission at the end of radiotherapy, one had partial response, and three had stable disease. All patients remain relapse-free with time of follow-up ranging between 6.3-109.3 months from the end of therapy (median 24 months). CONCLUSION: None of the five patients with residual disease following chemotherapy demonstrated disease progression following chemotherapy and radiotherapy. Future prospective clinical trials are needed in order to test the possibility of treating germinomas patients who have residual disease after chemotherapy with a low dose of radiotherapy similar to that used in patients with complete remission.